Congenital Hyperinsulinemic Hypoglycaemia of Infancy- A Case Report - Mani Raj; KARTHIKEYAN KADIRVEL; Sumathisri Ramachandran (JCDR Research and Publications Pvt. Ltd., 2021)
The most common cause for neonatal persistent hypoglycemia is Congenital hyperinsulinism (CH) which is characterised by low blood glucose with an inappropriately higher insulin level. A one-day-old male baby, third born to non-consanguineous parents delivered at term, small for gestational age, detected to have hypoglycaemia at 24 hours of life. He was established on breastfeed. Glucose infusion was started initially with Glucose Infusion Rate (GIR) of 4 mg/kg/min and increased according to the blood glucose values. Euglycaemic state was achieved with GIR of 14 mg/kg/min and intravenous hydrocortisone. Critical blood samples were sent when GIR was at 8 mg/kg/min which showed detectable insulin with high ammonia and normal cortisol levels. Hence, the diagnosis of transient hyperinsulinemic hypoglycaemia of infancy with hyperammonemia was considered and treated with oral diazoxide and sodium benzoate. GIR could be tapered and was discharged on breastfeed and medications. During follow-up at three months of age, the medications were stopped under glucose monitoring. He had normal growth and development at 12 months of age. Neonatal hypoglycaemia should be aggressively managed to prevent neuroglycopenia and its resultant neurodevelopmental disability. When GIR is more than 8 mg/kg/min, hyperinsulinism should be suspected for appropriate therapy